2012
DOI: 10.1073/pnas.1210344109
|View full text |Cite|
|
Sign up to set email alerts
|

Reduced sensitivity to emotional prosody in congenital amusia rekindles the musical protolanguage hypothesis

Abstract: A number of evolutionary theories assume that music and language have a common origin as an emotional protolanguage that remains evident in overlapping functions and shared neural circuitry. The most basic prediction of this hypothesis is that sensitivity to emotion in speech prosody derives from the capacity to process music. We examined sensitivity to emotion in speech prosody in a sample of individuals with congenital amusia, a neurodevelopmental disorder characterized by deficits in processing acoustic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
107
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 58 publications
(72 reference statements)
11
107
3
3
Order By: Relevance
“…However, recent findings question the domain specificity of the present findings. First, a mild deficit in identifying happiness and sadness from speech prosody has been observed in congenital amusia (Thompson, Marin, & Stewart, 2012). Second, the spectra of M A N U S C R I P T…”
Section: Discussionmentioning
confidence: 99%
“…However, recent findings question the domain specificity of the present findings. First, a mild deficit in identifying happiness and sadness from speech prosody has been observed in congenital amusia (Thompson, Marin, & Stewart, 2012). Second, the spectra of M A N U S C R I P T…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, difficulties with music are not the only characteristics of individuals with amusia (amusics). Studies have shown that the perception and production of pitch changes in the linguistic domain may likewise be problematic for amusics, although to a less pronounced extent (e.g., Patel et al, 2008;Liu et al, 2010;Tillmann et al, 2011a;Liu et al, 2012;Thompson et al, 2012;Liu et al, 2013). However, the precise nature of amusia, or rather, of the deficits that underlie amusia, is not well understood.…”
Section: Introductionmentioning
confidence: 94%
“…, 2012). The condition was originally described as a strictly musical deficit, but this specificity has been challenged by recent evidence for deficits in prosody perception in both non-tonal (Patel et al ., 1998; Patel et al ., 2008; Thompson et al ., 2012) and tonal (Jiang et al, 2010; Jiang et al ., 2012a) languages, as well as categorical perception of language tones in Mandarin speakers (Jiang et al ., 2010; 2012b). The diagnostic tool most widely used for congenital amusia is the Montreal Battery of Evaluation of amusia (MBEA, Peretz et al ., 2003), which consists of six tests that assess musical pitch and rhythm discrimination, meter perception and memory.…”
Section: Introductionmentioning
confidence: 99%